EVALUATION OF COMMUNITY SATISFACTION THROUGH SERVICE QUALITY SERVICES AND SERVICE DIFFERENCE BEHAVIOR AT CLASS II IMMIGRATION OFFICE TPI LHOKSEUMAWE - Hamdiah, Hamdiah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This practice report aims to evaluate community satisfaction through a survey of service quality and service deviation behavior at the Immigration Office Class II TPI Lhokseumawe in order to create a new face of the immigration service bureaucracy and improve service quality related to information on requirements, procedures/flows, time for completion of tariffs/fees, infrastructure, response, consultation and complaints, as well as reducing service deviation behavior related to discrimination, fraud, gratification, extortion, and brokers. The data used in the survey of service quality and service deviation behavior at the Class II Immigration Office of TPI Lhokseumawe are primary data and interviews with several informants who are experts in their fields. The location of the practice was carried out at the Class II Immigration Office of TPI Lhokseumawe. The data collection techniques used were: interviews, document studies and observation. The survey results in this practice report are 98.27 (IKM) and 99.08 (GPA) in the March period, 96.67 (IKM) and 97.90 (GPA) in the April period. 94.80 (IKM) and 92.43 (GPA) in the period of May, and 97.69 (IKM) and 99.80 (G.P.K.) in the period of June. (88.31 100.00) seen from the aspect of the Community Satisfaction Index (IKM) and from the aspect of the Corruption Perception Index (GPA).